Management of two osteomas in the frontoethmoidal region using an osteoplastic flap, endoscopic approach and 3D CT imaging - Hypnar, Julia; Rudziński, Marcin; Magdziarz, Mateusz; Pośpiech, Jakub; Możdżeń, Kamil; Błażejowski , Michał; Przeklasa, Maria; Hartwich, Patryk; Konior, Marcin; Tomik, Jerzy (Folia Medica Cracoviensia, 2026)
The aim of this study was to demonstrate the application of preoperative three-dimensional (3D) computed tomography (CT) reconstruction in the surgical management of paranasal sinus (PNS) osteomas. Osteomas are the most common benign PNS tumors and can lead to significant symptoms, including chronic rhinosinusitis, frontal pressure, and orbital or intracranial complications. Surgical excision is recommended for symptomatic cases or those with potential complications, with endoscopic and external approaches being the primary techniques. A 74-year-old patient presented with symptoms of chronic rhinosinusitis, including nasal obstruction and anosmia. CT revealed osteomas in the left ethmoid and frontal sinuses, measuring 27 × 21 × 28 mm and 15 × 17 mm, respectively. The patient was qualified for surgical excision of lesions. Preoperative planning included 3D CT reconstruction to assess the osteomas’ size, location, and surgical access, particularly for a planned osteoplastic flap (OPF). During surgery, an endoscopic approach was initially utilized, resulting in frontosphenoethmoidectomy and removal of ethmoid osteoma. The other osteoma extended from the anterior to the posterior wall of the frontal sinus and required conversion to an external approach using the preplanned OPF. The surgery was successfully completed, with intraoperative findings being consistent with imaging. Postoperative complications were limited to frontal sinus outflow stenosis, managed endoscopically during follow-up. PNS osteomas may require complex surgical planning, especially when endoscopic and external approaches are combined. Preoperative 3D CT reconstruction provides valuable insights into tumor characteristics and aids in precise surgical planning. This case highlights the utility of 3D imaging in safe and effective management of challenging PNS osteomas.